Contextualising the Hyflex Model of Instruction for Language Classes - Robert Oliwa (Theory and Practice of Second Language Acquisition, 2024)
The paper discusses a possible, practical application of the hybrid flexible (hyflex) model of content delivery in a tertiary context. The model may as well be applied in foreign language instruction. It is the author’s belief that there are convincing reasons for employing digital competences and skills acquired over the last two years to enhance teaching and learning. AnMappropriate contextualisation of the hyflex model may further encourage the retention of theMalready attained competences and skills in the new normal. It may also allow to combine the traditional, in-class instruction with the new, online interaction both synchronously and asynchronously. The possibility of hyflexing language courses can be a challenging, however responsible, prospect because the restoration of the education we used to know might not be easy. Although theoretical, the paper provides practical guidelines as well as offers a selection of online tools to contextualise the hyflex model in language teaching. The paper may also constitute a strong claim for the practical application of the hyflex model especially when combined with an in-depth analysis and research of the model in various educational contexts. As the future is hard to envisage, various models and approaches might be taken into account so as to appropriately respond to the challenges and requirements education is likely to be confronted with.